Primary yolk sac tumor (endodermal sinus tumor) of the vulva: case report and review of the literature - (:unkn) unknown (I R O G CANADA, INC, 2006)
Introduction: Endodermal sinus tumor (EST) or primary yolk sac tumor (YST) of the vulva is extremely rare and a highly malignant germ cell tumor. Only nine cases of vulvar YST have been reported to the world literature to date. We present the tenth case of endodermal sinus tumor of the vulva. Case: A 32-year-old white virgin presented with a 3.5 cm right labial mass without any other signs or symptoms. Excisional biopsy showed YST with a predominantly solid pattern. Unilateral hemivulvectomy with bilateral inguinal lymphadenectomy was performed. Six months after surgery there was a recurrence. She was treated with three courses of the BEP regimen (bleomycin, etoposide, cisplatin). The patient refused to take any further treatment including radiotherapy. The serum alpha-fetoprotein (AFP) was not elevated at the initial diagnosis however it was elevated during recurrence. The patient is alive with the disease 42 months after the first appearance of the vulvar mass.
Keywords: yolk sac tumor; endodermal sinus tumor; vulva; CHEMOTHERAPY